Evaluation of follicular T‐helper cells in primary cutaneous CD4+ small/medium pleomorphic T‐cell lymphoma and dermatitis. (12th October 2013) - Ally, Mina S.; Prasad Hunasehally, Ranganna Y.; Rodriguez‐Justo, Manuel; Martin, Blanca; Verdolini, Roberto; Attard, Natalie; Child, Fiona; Attygalle, Ayoma; Whittaker, Sean; Morris, Stephen; Robson, Alistair
<x xml:space="preserve">Abstract</x> Background CD4+ small/medium‐sized pleomorphic T‐cell lymphoma (SMPTCL) is a controversial primary cutaneous lymphoma, in which the candidate neoplastic cells express a follicular T‐helper phenotype. We describe 16 cases of SMPTCL and compare expression of PD‐1, CXCL‐13 and ICOS in these tumors with 40 dermatitis cases. Methods Histopathologic examination and immunocytochemistry were performed for 16 tumors and 40 assorted dermatitis cases. Results All but one patient presented with solitary lesions. Each biopsy revealed a dense nodular non‐epitheliotropic infiltrate of atypical T‐cells. Neoplastic cells were CD3+/CD4+/CD8(−)/CD30(−). Cutaneous recurrence occurred in one patient over a median follow up of 8 months (range 5–36). All tumors widely expressed PD‐1 and ICOS to a lesser extent. CXCL‐13 stained much fewer cells. Of the dermatitis cases, PD‐1 (most numerous) and ICOS labeled lymphoid cells in all cases, albeit fewer than in the tumors, and CXCL‐13 was negative in 32. A rosette pattern of PD‐1 expression was identified in all the SMPTCL cases but not in dermatitis. Conclusions There remains uncertainty about the appropriate nosological status of SMPTCL, which some authors consider to be a pseudolymphoma. However, this study suggests a significant difference in the prevalence and pattern of follicular T‐helper cell markers between this tumor and lymphoid proliferations known to be reactive.